2017
DOI: 10.1097/cad.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxoline shows antimyeloma activity by targeting the TRIM25/p53 axle

Abstract: The aim of this study was to identify the most potent quinoline-based anti-infectives for the treatment of multiple myeloma (MM) and to understand the molecular mechanisms. A small-scale screen against a panel of marketed quinoline-based drugs was performed in MM cell lines. Cell apoptosis was examined by flow cytometry. Anti-MM activity was also evaluated in nude mice. Western blotting was performed to investigate mechanisms. Nitroxoline (NXQ) was the most effective in suppressing MM cell proliferation. NXQ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…MM cells were infected with lentiviral UBE2O for 1 - 7 d before being subjected to MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay as described previously [17, 18]. …”
Section: Methodsmentioning
confidence: 99%
“…MM cells were infected with lentiviral UBE2O for 1 - 7 d before being subjected to MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay as described previously [17, 18]. …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, nitroxoline was found to induce apoptosis in multiple myeloma (Mao et al, 2017). Similar to that as in glioma cells, treatment of multiple myeloma cell lines with nitroxoline activated caspase 3 in a concentrationdependent manner and caused cleavage and inactivation of PARP, as well as of deactivated survival proteins such as Bcl-xL and Mcl-1.…”
Section: Antitumor Activity Of Nitroxolinementioning
confidence: 72%
“…Similar to that as in glioma cells, treatment of multiple myeloma cell lines with nitroxoline activated caspase 3 in a concentrationdependent manner and caused cleavage and inactivation of PARP, as well as of deactivated survival proteins such as Bcl-xL and Mcl-1. Additionally, in multiple myeloma, nitroxoline was suggested to affect apoptosis by concentration-dependent downregulation of a triple motif containing 25 (TRIM25)/p53 axle (Mao et al, 2017). The protein encoded by the TRIM25 gene is a member of the tripartite motif (TRIM) family ubiquitin ligases.…”
Section: Antitumor Activity Of Nitroxolinementioning
confidence: 99%
“…Nitroxoline, an FDA‐approved antibiotic, was identified to display antitumor activity, which was considered to be repurposed for tumor therapy . A recent study reported that NXQ was screened out to show antimyeloma activity both in vitro and in vivo by targeting the TRIM25/p53 axis . In cholangiocarcinoma cells, NXQ also exhibited anticancer activity by inducing FoxM1 inhibition .…”
Section: Discussionmentioning
confidence: 99%
“…13 A recent study reported that NXQ was screened out to show antimyeloma activity both in vitro and in vivo by targeting the TRIM25/ p53 axis. 14 In cholangiocarcinoma cells, NXQ also exhibited anticancer activity by inducing FoxM1 inhibition. 15 NXQ was also considered as a potent and selective inhibitor of cathepsin B, hence reducing glioma tumor progression in vitro and in vivo, and a number of derivatives of NXQ were developed by using structure-based chemical synthesis in order to further improve its antitumor properties.…”
Section: Discussionmentioning
confidence: 99%